Early Opiate Analgesic Requirements Following Nonsurgically Managed Tibial Fractures in Children. Issue 8 (12th September 2021) - Yap, Rye Y.; Sultan, Sanaah; Ahmad, Husham; Marson, Ben; Ikram, Adeel; Ollivere, Benjamin; Lawniczak, Dominik
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Many children with tibial fractures are currently being managed as outpatients. It is unclear how much opiates should be prescribed to ensure adequate analgesia at home without overprescription. This study aimed to evaluate the risk factors for requiring opiates following admission for tibial fractures and to estimate opiate requirements for children being discharged directly from the emergency department (ED). Methods: All children aged 4 to 16 years admitted with closed tibial fractures being treated in a molded circumferential above-knee plaster cast between October 2015 and April 2020 were included. Case notes were reviewed to identify demographics, analgesic prescriptions, and complications. Risk factors were analyzed using logistic regression. Results: A total of 75 children were included, of which 64% were males. The mean age was 9.5 (SD 3.4) years. Opiates were required by 36 (48%) children in the first 24 hours following admission. The median number of opiate doses in the first 48 hours was 0 (range: 0 to 5), with 93% of children receiving ≤3 doses. The odds of requiring opiates in the first 24 hours were unchanged for age above 10 years [odds ratio (OR)=0.85, 95% confidence interval (CI): 0.33-2.23], male sex (OR=1.58, 95% CI: 0.59-4.19), high-energy injury (OR=1.65, 95% CI: 0.45-6.04), presence of a fibula fracture (OR=2.21, 95% CI: 0.72-6.76), or need for fracture reduction in the ED (OR=0.57, 95% CI: 0.20-1.65). No children developed compartment syndrome, and the mean length of stay was 1.4 (SD 1.2) days. No children were readmitted following discharge. Conclusions: We have found no cases of compartment syndrome or extensive requirement for opiates following closed tibial fractures treated in plaster cast. These children are candidates to be discharged directly from the ED. We have not identified any specific risk factors for the targeting of opiate analgesics. We recommend a guideline prescription of 6 doses of opiates for direct discharge from the ED to ensure adequate analgesia without overprescription. Level of Evidence: Level IV—case series.